2010
DOI: 10.1111/j.1464-5491.2010.03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among patients hospitalized for Type 1 diabetes mellitus: a population‐based cohort study in Sweden

Abstract: By quantifying the variations of overall and site-specific cancer risks after T1DM, the current study provides novel associations between T1DM and subsequent cancers, the mechanisms of which remain to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 31 publications
(48 reference statements)
5
94
0
1
Order By: Relevance
“…Some studies included type 1 and type 2 diabetes, which would lead to an attenuation of the risk estimates if only type 2 diabetes is a risk factor for kidney cancer. In fact, a population-based cohort study in Sweden found no excess risk of kidney cancer in hospitalised type 1 diabetes patients [32]. Moreover, because total kidney cancer was assessed in most studies, the overall association would be attenuated if diabetes were a risk factor for renal cell (parenchyma) or renal pelvis cancer only.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies included type 1 and type 2 diabetes, which would lead to an attenuation of the risk estimates if only type 2 diabetes is a risk factor for kidney cancer. In fact, a population-based cohort study in Sweden found no excess risk of kidney cancer in hospitalised type 1 diabetes patients [32]. Moreover, because total kidney cancer was assessed in most studies, the overall association would be attenuated if diabetes were a risk factor for renal cell (parenchyma) or renal pelvis cancer only.…”
Section: Discussionmentioning
confidence: 98%
“…However, all three studies failed to meet the inclusion criteria with two studies failing to include an internal control group (Zendehel et al 2003, Shu et al 2010 while one study assumed a diagnosis of type 1 diabetes mellitus in all patients aged under 35 years without confirmation (Baron et al 2001). Interestingly, the studies were homogenous in their finding of a protective risk point estimate despite none of the studies reaching statistical significance.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 89%
“…1). Eleven studies were excluded for failing to include an internal control group (De Waard & Baanders Van Halewijn 1974, Ragozzino et al 1982, Adami et al 1991, Hjalgrim et al 1997, Weiderpass et al 1997, Wideroff et al 1997, Kath et al 2000, Zendehel et al 2003, Swerdlow et al 2005, Shu et al 2010, three studies were excluded for investigating mortality rather than incidence (Coughlin et al 2004, Siegelmann-Danieli et al 2006, Tseng et al 2009), one study was excluded for using benign breast disease as a comparator (Muck et al 1975) and the final study was excluded for investigating the effect of glycaemic control on BC incidence (Stefansdottir et al 2011). The remaining 43 studies were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of type 1 diabetes cohorts, compared with the general population, suggest increased risks in some cancers (for example, ovarian cancer in a UK series [24]), but these are not consistent across all studies [24][25][26][27]. Notably, there does not appear to be associations between type 1 diabetes and the cancers linked with type 2 diabetes-i.e.…”
Section: Epidemiology Of Diabetes and Cancer Incidencementioning
confidence: 95%